Embodied Spatial Knowledge Acquisition in Immersive Virtual Reality: Comparison to Map Exploration - König, Sabine U.; Keshava, Ashima; Clay, Viviane; Rittershofer, Kirsten; Kuske, Nicolas; König, Peter (Frontiers in Virtual Reality, 2021)
Investigating spatial knowledge acquisition in virtual environments allows studying different sources of information under controlled conditions. Therefore, we built a virtual environment in the style of a European village and investigated spatial knowledge acquisition by experience in the immersive virtual environment and compared this to the use of an interactive map of the same environment. The environment was well explored with both exploration sources covering the whole village area. We tested knowledge of cardinal directions, building-to-building orientation, and judgment of direction between buildings in a pointing task. Judgment of directions was more accurate after exploration of the virtual environment than after map exploration. The opposite results were observed for knowledge of cardinal directions and relative orientation between buildings. Time for cognitive reasoning improved task accuracies after both exploration sources. Further, an alignment effect towards north was only visible after map exploration. Taken together, our results suggest that the source of spatial exploration differentially influenced spatial knowledge acquisition.